Studies on the Binding of 3H-SR121566, an Inhibitor of Gp IIb-IIIa Activation - Savi, P.; Zamboni, G.; Rescanières, O.; Herbert, J. M. (Thrombosis and Haemostasis, 2001)
SR121566 is a new synthetic agent which inhibits the binding of fibrinogen to activated platelets, and platelet aggregation. 3H-SR121566 bound with nanomolar affinity (KD ranging from 45 to 72 nM) to Gp IIb-IIIa expressing cells only. On activated human platelets, this ligand allowed the detection of a maximal number of 100-140,000 binding sites. The binding of SR121566 to platelets, was displaced by several agents including RGD-containing peptides and synthetic RGD mimetics, but not by ReoPro®, a humanised monoclonal antibody which inhibits the binding of fibrinogen to the Gp IIb-IIIa complex. Neither the fibrinogen dodecapeptide nor fibrinogen itself were able to compete with SR121566 whether platelets were activated or not.Flow cytometry studies indicated that SR121566 which did not activate Gp IIb-IIIa by itself, dose-dependently prevented the detection of activation-induced binding sites on TRAP-stimulated platelets in the presence or absence of exogenous fibrinogen, indicating a direct effect on the activation state of the Gp IIb-IIIa complex. Moreover, SR121566 was able to reverse the activation of Gp IIb-IIIa and to displace the binding of fibrinogen when added up to 5 min after TRAP stimulation of platelets. When added at later times (15 to 30 min), SR121566 failed to displace fibrinogen binding, even if SR121566 binding sites were still accessible and the Gp IIb-IIIa complex not activated.In conclusion, our study is in accordance with the finding that fibrinogen is recognised by the activated Gp IIb-IIIa complex through the dodecapeptide sequence present on its gamma chain, and that this interaction is inhibited by SR121566 by preventing and reversing the activated conformation of Gp IIb-IIIa and not by direct competition with fibrinogen.
Keywords: Human platelets; anti-Gp IIb-IIIa; Gp IIb-IIIa activation